INTERTEXT. LITERATURE BETWEEN NATIONAL CULTURES - Dąbrowski, Mieczysław (Porównania, 2013)
This article is part of a larger whole. Its aim is to provide critical overview of the emigration literature of the 1980s (the so- called post-Solidarity or political emigration) and the 1990s (the first wave of economically and culturally motivated of migration, repeated after the Polish accession to the EU). Most importantly, both sets of texts record the cultural experience of migration. The analyzed exam ples of prose (by J. Rudnicki and K. M. Załuski) allow to pre-recognize the poetics and the problem of the intertext. There are two main elements of its construction and interpretation: understanding the experience of emigration as intercultural experience and the conscious design of the text as a dialogical text.